2015
DOI: 10.1038/eye.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Results of conservative management for consecutive esotropia after intermittent exotropia surgery

Abstract: Purpose To examine the clinical course of consecutive esotropia (ET) using conservative management, after intermittent exotropia (IXT) surgery. Methods This study included 149 out of 151 consecutive patients with ET after IXT surgery, who were managed conservatively. The clinical course of consecutive ET was examined and the patients were classified into two groups based on the duration of esodeviation: (1) 43 weeks (persistent ET group, n = 56) and (2) o3 weeks (transient ET group, n = 93). Patient characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Mild surgical overcorrection immediately after IXT surgery can be transient because of the exodrift that typically occurs with time [ 7 12 15 23 ]. Consecutive esotropia, however, can result from persistent overcorrection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild surgical overcorrection immediately after IXT surgery can be transient because of the exodrift that typically occurs with time [ 7 12 15 23 ]. Consecutive esotropia, however, can result from persistent overcorrection.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive overcorrection and consecutive esotropia after surgery for IXT can cause diplopia. In children it can also lead to worsening stereopsis and amblyopia, indicating the need for timely and proper treatment [ 15 16 ].…”
mentioning
confidence: 99%
“…Persistent consecutive esotropia could be managed in the following manner. First, prism glasses could be helpful to maintain fusion; however, despite its advantage, it requires considerable time to wean off of prism glasses [4][5][6]. Second, long-standing persistent consecutive esotropia may ultimately require additional surgery; however, long-term results of surgery for consecutive esotropia remain highly variable and unpredictable [7].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal time and indications for botulinum toxin injection in consecutive esotropia remain unclear [10]. Considering the natural exodrift after exotropia surgery, it is likely that small angles of esotropia may resolve spontaneously over time [3,4]. Park et al have shown that more than 50% of the total amount of exodrift was observed within the first postoperative year, but no subsequent changes were observed after 3 years [21].…”
Section: Plos Onementioning
confidence: 99%
“…Initial overcorrection is a common outcome of surgical treatment of intermittent exotropia, as it is considered as a good prognostic factor for long-term surgical success of intermittent exotropia [1,2]. While most patients with initial postoperative overcorrection gradually improve due to postoperative exodrift after exotropia surgery [3,4], persistent consecutive esotropia may be intolerable to patients or their parents. Persistent consecutive esotropia could be managed in the following manner.…”
Section: Introductionmentioning
confidence: 99%